Proteolytic Disassembly of Viral Outer Capsid Proteins Is Crucial for Reovirus-Mediated Type-I Interferon Induction in Both Reovirus-Susceptible and Reovirus-Refractory Tumor Cells. (19th March 2015) - Katayama, Yuki; Terasawa, Yuichi; Tachibana, Masashi; Mizuguchi, Hiroyuki; Sakurai, Fuminori
Abstract : Oncolytic reovirus induces innate immune responses, which contribute to the antitumor activity of reovirus, following in vivo application. Reovirus-induced innate immune responses have been relatively well characterized in immune cells and mouse embryonic fibroblasts cells; however, the mechanisms and profiles of reovirus-induced innate immune responses in human tumor cells have not been well understood. In particular, differences in reovirus-induced innate immune responses between reovirus-susceptible and reovirus-refractory tumor cells remain unknown, although the intracellular trafficking of reovirus differs between these tumor cells. In this study, we examined reovirus-induced upregulation of interferon- (IFN-) β and of the proapoptotic gene, Noxa, in reovirus-susceptible and -refractory tumor cells. IFN- β and Noxa were significantly induced by reovirus via the IFN- β promoter stimulator-1 (IPS-1) signaling in both types of tumor cells. Inhibition of cathepsins B and L, which are important for disassembly of reovirus outer capsid proteins and escape into cytoplasm, largely suppressed reovirus-induced upregulation of IFN- β and Noxa expression in not only reovirus-susceptible but also reovirus-refractory tumor cells. These results indicated that in both reovirus-susceptible and reovirus-refractory tumor cells, disassembly of the outer capsid proteins by cathepsins and the escape into the cytoplasm were crucial steps for reovirus-induced innate immunity.